Aspectos socioambientais do turismo na praia do porto das Dunas, no município de Aquiraz - CE - Rios, Roberta de Lavor (2006)
The tourist activity is inserted in the sector of services and emerges as one important component in the economic dynamics of today in the State of the Ceará, being considered a governmental priority. In result of the current model of economic development adopted by the industrial capitalist society, it is observed occupation and irregular exploration of the pertaining to the state of Ceará littoral spaces for this activity, causing serious related socioambientais impacts to the use of the landscape and the available natural resources, and shaking the relations between society and nature. This attention directed toward the practical one of the tourism in the coastal zone elapses of the tourist potential and of it offers diversified of its attractive natural ones. In this principle, objective it analysis of the socioambientais aspects of the tourism in the beach of the Port of Dunes, in the City of Aquiraz, situated in the Region Metropolitan of Fortaleza, coast east of the pertaining to the state of Ceará coast. Intent for an understanding of decurrent the positive and negative impacts of the practical one of the tourist activity in the mentioned beach, by means of a generic analysis of the relation of cost-benefits of the development of the tourism for the region the binomial tourism-environment under the optics of the sustainable development. Using itself of a descriptive, investigative and exploratory boarding methodological. In Ioco had been collected given primary by means of photographic registers, semidirected interviews and application of questionnaires next to that they inhabit in neighborhoods of the great tourist equipment of the region, to the tourists and entrepreneurs of the tourism. Later, a quail-quantitative analysis of secondary data gotten by bibliographical research was become fullfilled and registers specific. By means of the interpretation of the data, it was concluded to conclude that the majority of the interviewed ones little knows the attractive places or if involves in fact in the practical one of the tourism, being isolated for the artificial barriers of resorts beyond showing that the costs are bigger of what the benefits generated for the population. It is evidenced, still, the necessity of the implantation of public politics of tourism directed toward the sustainability of the activity in the region, searching to transform and to adjust the destination Port of Dunes, to the increasing flow of the demand of external tourist markets as well as to not only improve the quality of life of the resident population. Antropic actions expect that, as social exclusion, socioespacial segregation, loss of the identity o the local culture, second residences, real estate speculation, supervaluation of the littoral zone, irregular dune occupation, amongst others, can be mitigated by means of the strategical planning, demonstrating that still it has hope to reach the sustainability so desired in the spheres social, ambient and economic.